An Action-oriented Understanding of Reflection - Petersen, Inge-Kathrine (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This paper explores commonalities in antecedents, context, process, outcomes, and techniques that foster action-oriented Reflection through the pragmatic methodological processing of reflection theories from Mezirow, Dewey, Schön, and Reflective Practice-based Learning. Despite the widespread adoption of reflective practices across various fields of study and practice, reflection remains a complex and challenging concept to comprehend. One of the reasons why reflection is difficult to understand is that the scientific work around reflection has often focused on defining different conceptions of reflection using different semantics. When researchers study reflection, they tend to analyze definitions of reflection instead of focusing on the phenomenon of reflection itself. Semantically rooted definitions represent how we should act, and not necessarily what happens when reflection occurs. Signs of actions in reflection across the theories and Reflective Practice-based Learning are analyzed and presented as a theoretical model for Action-oriented Reflection. The model visualizes the process from pre-reflective sensing to the effect of reflective actions.